2016
DOI: 10.1007/s10554-016-0851-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aortic stiffness among patients with systemic lupus erythematosus and rheumatoid arthritis by magnetic resonance imaging

Abstract: To evaluate aortic stiffness by MRI in female patients with systemic lupus erythematosus (SLE) or rheumatoid arthritis (RA) in comparison to controls. We measured aortic strain, distensibility and pulse wave velocity (PWV) by MRI in 30 SLE patients, 31 RA patients and 53 matched controls. Mean PWV in SLE and RA patients were higher in comparison to controls (9.2 ± 4.4 vs. 7.6 ± 3.0 m/s, p = 0.04) and (6.2 ± 2.3 vs. 5.4 ± 1.7, p = 0.04) respectively. Aortic distensibility among RA patients was significantly low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
0
8
1
Order By: Relevance
“…However, the effect of age on PWV, mediated by SBP and BMI, has not been previously described. On the other hand, distensibility is not as well-studied as a marker of arterial stiffness in RA patients 25,26 , and the association between BMI and sex observed in our study has not been previously published.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…However, the effect of age on PWV, mediated by SBP and BMI, has not been previously described. On the other hand, distensibility is not as well-studied as a marker of arterial stiffness in RA patients 25,26 , and the association between BMI and sex observed in our study has not been previously published.…”
Section: Discussioncontrasting
confidence: 65%
“…Some case-control studies reported increased arterial stiffness in RA patients 11–13 . In these studies, associations with variables that are characteristic of the disease such as disease duration 14,15 , inflammatory variables 1619 , and disease activity 16,20–22 have been demonstrated, although arterial stiffness has also been correlated with age 19,23,24 and SBP 2325 . There are few published studies that have evaluated distensibility as a marker of arterial stiffness in RA 26 , and the results of these studies are similar to those obtained for PWV and AIx.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to myocardial hypertrophy within physiological range in non-CKD group [12,40,41], the marked structural remodeling in CKD is accompanied with myocardial diffuse fibrosis and dysfunction. In CKD, native T1 is higher at any given PWV implying potentiation of the adverse remodeling with worsening stages of CKD [10,11,42,43] (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies studies assessed the relationship between serum lipids and arterial stiffness in RA patients, they found that hyperlipidemia did not significantly correlate with aortic stiffness as measured by carotid femoral pulse wave velocity (cfPWV). 27 , 28 But when the components of the lipids were considered separately, aortic stiffness showed direct associations only with triglycerides. 29 …”
Section: Discussionmentioning
confidence: 98%